The Effect of Project Activity Cooperative Exercise (PACE) Learning Model on Students’ Mathematical Communication Skills in Science Integrated Mathematics Education - Reka Afrillia Zeni; Edwin Musdi; Laswadi; Eline Yanty Putri Nasution; Romi Kurniawan (Postgraduate, University of Mataram, 2026)
This quasi-experimental study examined the effect of the Project, Activity, Cooperative Learning, and Exercise (PACE) model on eighth-grade students' mathematical communication ability in solid geometry. Forty students from SMPN 6 Model Kota Sungai Penuh were assigned to an experimental group (PACE model) and a control group (conventional instruction). Both groups received six learning sessions on cubes and cuboids, followed by a six-item essay test assessing three communication indicators: written text, drawing, and mathematical expressions. Data analysis using independent samples t-test revealed the experimental group achieved a significantly higher mean score (81.25, high category) compared to the control group (73.125, moderate category); t(38) = 2.899, p = 0.006. The rejection of the null hypothesis confirmed that PACE implementation positively influenced students' ability to express mathematical ideas through verbal explanations, accurate visual representations, and appropriate symbolic notations. The model's project-based and collaborative components effectively scaffolded students' articulation of geometric concepts, demonstrating its pedagogical value for enhancing mathematical discourse in Indonesian lower secondary classrooms.